Study on The Soil Stabilization for Soft Soil Bearing Capasity Improvement using Lime Stabilizer - Chai, Ming Ya (2017)
Chemical stabilization method has been extensively used for the improvement of the weak soil, in improving the bearing capacity as well as the settlement of the soil. Plenty of researches regarding the effectiveness of using industrial waste as a chemical stabilizer are also increased rapidly. The aim of this research is to evaluate the engineering properties of the Bandar Seri Damansara weak soil using lime stabilizer at varies stabilizer contents (5%, 10%, 15% , 20%). Classification of soil such as Atterberg test, sieve analysis and standard proctor test were carried out to determine the properties, optimum moisture content and maximum dry density of the untreated soil. The basic properties of soil such as Unconfined Compressive Strength (UCS), Direct Shear test and also Consolidation test were used to gauge the behaviour and the performance of the stabilized soil. The carried out tests gave some indication the unconfined compressive strength and the direct shear test increase with the increase of percentage of lime stabilizer. As conclusion, the result shows that the stabilized soil sample achieves its optimum strength at 10% of lime stabilizer content. At 15% of lime stabilizer content the strength begin to drop as lime stabilizer is excessive.